Comparative Analysis of the Impact of Inventory Management on Organizational Performance - Fitridiani, Mutiara; Anggraeni Purnama Sari, Indah (International Journal of Innovation Research in Education, Technology and Management, 2025)
This study aims to examine the impact of inventory management practices on organizational performance through a literature review of five scholarly articles. The reviewed articles are from developing countries such as Indonesia, Ethiopia, Kenya, Uganda and Zimbabwe, covering diverse sectors like retail, manufacturing, and mining. The analysis reveals that inventory management practices consistently have a positive influence on operational efficiency and organizational competitiveness. Furthermore, managerial knowledge is identified as a mediating variable that strengthens the relationship between inventory practices and organizational performance. These findings highlight the crucial role of human resource capability in ensuring inventory management effectiveness beyond systems and procedures.